DNM1L‐related encephalopathy in infancy with Leigh syndrome‐like phenotype and suppression‐burst. Issue 5 (14th June 2016) - Zaha, K.; Matsumoto, H.; Itoh, M.; Saitsu, H.; Kato, K.; Kato, M.; Ogata, S.; Murayama, K.; Kishita, Y.; Mizuno, Y.; Kohda, M.; Nishino, I.; et al.
Abstract :